Evaluation of the hypertensive patient. Experience obtained in the blood pressure specialized consultation. - Margarita Roméu Escobar; Darelis Sabina Molina; Beatriz Sabina Roméu (Medisur, 2005)
Introduction: In the National Program of Arterial Hypertension Control it was proposed to habilitate specialized consultation units in Health Primary Attention to carry out the study of patients with hard to control hypertension or with suspicion of secondary arterial hypertension or refractory to treatment hypertension. The units have not been implanted in the policlinics of the province of Cienfuegos for what to evaluate the results of one of them turns to be an investigation task to meet its utility. Objectives: To corroborate the utility of these units in a given area for the study of the patients with the before mentioned characteristics of hypertension. Methods:There were included 80 patients with hypertension which assisted systematically, among the relocated to the specialized consultation at the policlinic ¨Octavio de la Concepcion y de la Pedraja¨ from January 2002 to January 2003. Each patient was interrogated, physically examined and investigated. They were revaluated periodically until their compensation or up to the decision of continuing special studies . Results: Only the 46.25% fulfilled the treatment correctly. It was found high prevalence of vascular risk factors. It was identified intensive retinopathy on 62.5% of the patients, cardiovascular repercussion on 40%, and renal repercussion on 25%. Two patients had secondary hypertension. The 72.5 of the patients could be compensated. Conclusion: The unit specialized in arterial hypertension of the health primary attention came to be very useful, for the patients could be diagnosed with secondary hypertension; besides, we could better by far the fulfilment of the treatment and compensate the majority.